Analysis of risk factors for Epstein–Barr virus reactivation and progression to post-transplant lymphoproliferative disorder in pediatric patients undergoing allogeneic hematopoietic stem cell transplantation - Jia, Lanzhou; Yang, Hui; Zhou, Ya; Meng, Yan; Zhang, Luying; Lei, Xiaoying; Guan, Xianming; Yu, Jie; Dou, Ying (Frontiers in Pediatrics, 2025)
BackgroundPost-transplant infections are common complications, and the reasons are pre-transplant conditioning, time required for post-transplant immune reconstitution, and use of immunosuppressive agents. We aimed to analyze the risk factors for Epstein–Barr virus (EBV) reactivation and its progression to post-transplant lymphoproliferative disorder (PTLD) following allogeneic hematopoietic stem cell transplantation (allo-HSCT) in children and to determine the EBV PCR diagnostic threshold for PTLD.MethodsWe retrospectively analyzed clinical data of 309 patients who underwent allo-HSCT without engraftment failure at the Children's Hospital of Chongqing Medical University from January 1, 2016, to December 21, 2021. The occurrences of EBV reactivation and PTLD were also recorded. The risk factors for EBV reactivation and progression to PTLD were analyzed, and the diagnostic threshold for PTLD was determined using whole-blood EBV PCR.ResultsAmong 309 pediatric patients, 256 experienced EBV reactivation within one year and 12 progressed to PTLD. Univariate and multivariate analyses indicated that ATG was the independent risk factor for EBV reactivation. Grade III-IV acute graft-vs.-host disease (aGVHD) was the risk factor for PTLD after EBV reactivation.ConclusionsPost-transplant EBV reactivation is a common complication after allo-HSCT, but rarely progresses to PTLD. Identification of the risk factors for PTLD and regular monitoring of the EBV-DNA load play important roles in prevention and cure of PTLD after HSCT.